TEACHER’S PERCEPTION TOWARD E-LEARNING EXPERIENCE - VERONIKA NAVA WAROKKA; Noldy Pelenkahu; Nihta Liando (Program Studi Pendidikan Bahasa Inggris, 2022)
The language skills play a crucial role in overall development in English knowledge and even in academic success. This improvement can be seen from the progressively diverse learning methods used and various media to move forward the quality of learning outcomes. The implementation of E- learning has become alternative arrangement for teachers and students to undergo the teaching and learning process, especially in the pandemic situation. It is expected to increase students' retention of the material being taught, increase students' dynamic participation, progress students' independent learning capacities, move forward the quality of instruction and preparing materials, increase the capacity to show data with data innovation gadgets. The purpose of the study is to describe teacher’s perception towards E-Learning implementation in EFL class. This study is a descriptive quantitative research because this research is to find out the teacher’s perception toward E-Learning implementation in EFL class. The result of the study leads to the following result: in the data from the respondents’ answer related to the teachers’ perceptions on implementation E-Leaning activities. The highest score was a percentage of (24.5%) agree with the questionnaire, and lowest was (4.2%) of teachers strongly disagree with implementation E-Leaning in English class. The data from questionnaire can be concluded, E-Learning as the one of learning media that uses information and communication technology.